Tinjauan Metode Pembangkitan Tegangan Tinggi AC: Pendekatan Pembangkitan yang Portabel dan Ekonomis : Tinjauan Metode Pembangkitan Tegangan Tinggi AC: Pendekatan Pembangkitan yang Portabel dan Ekonomis - M.Chaisar Al Furqon, Furqon (Institut Riset dan Publikasi Indonesia, 2024)
Although high voltage generation technology exists, its implementation in small-scale or portable applications remains a significant challenge. This underscores the urgent need to develop more accessible, flexible, and affordable high voltage generation technologies, particularly for field applications and small to medium-sized enterprises. This research reviews various existing methods of AC high voltage generation and evaluates their potential for portable and economical applications. Methods such as high-frequency inverters, Tesla coils, Marx generators, H-Bridge generators, switchable capacitor arrays, and dual flyback transformers are assessed for their portability and economic feasibility. The findings indicate that these reviewed AC high voltage generation methods offer practical and economical solutions for various applications, including plasma research, oil drilling, and medical applications. By leveraging compact and relatively inexpensive technologies, this research has the potential to enhance the efficiency and flexibility in developing high voltage generation systems for industrial and research purposes in the future.